2007
DOI: 10.1002/jbm.a.31689
|View full text |Cite
|
Sign up to set email alerts
|

In vitro engineering of a palatal mucosa equivalent with acellular porcine dermal matrix

Abstract: The objective of this study was to develop a palatal mucosa equivalent composed of multilayered oral keratinocytes grown on the acellular porcine dermal matrix. Acellular porcine dermal matrix was prepared through a series of procedures and assessed by histological, immunohistochemical, and scanning electron microscopy examination. The palatal mucosa equivalent was fabricated by seeding oral keratinocytes, which cultured from human palate mucosa, onto the acellular dermal matrix. After 4 days submerged in medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…In our previous study with our patented collagen-glycosaminoglycan-chitosan scaffold [14], we observed the same pattern: at the end of 3 weeks of culture, only a few proliferative cells (Ki67 positive) remained in the reconstructed oral mucosa [15]. Other studies on tissue-engineered oral mucosa also found that at the end of the culture period (even for cultures of only 11 days) either no proliferative cell [16] or only a few remained in the oral mucosal equivalents [13,17,18], which is much less than found in native oral mucosa. These results led the researchers to investigate into the mechanisms of various regenerative medicine approaches and epithelial stem cell biology [8].…”
Section: Introductionsupporting
confidence: 82%
“…In our previous study with our patented collagen-glycosaminoglycan-chitosan scaffold [14], we observed the same pattern: at the end of 3 weeks of culture, only a few proliferative cells (Ki67 positive) remained in the reconstructed oral mucosa [15]. Other studies on tissue-engineered oral mucosa also found that at the end of the culture period (even for cultures of only 11 days) either no proliferative cell [16] or only a few remained in the oral mucosal equivalents [13,17,18], which is much less than found in native oral mucosa. These results led the researchers to investigate into the mechanisms of various regenerative medicine approaches and epithelial stem cell biology [8].…”
Section: Introductionsupporting
confidence: 82%
“…The cultured oral keratinocytes used for the fabrication of mucosa equivalent were in passage 2 and the cell seeding concentration was adjusted to 5 × 10 5 cells/mL. The cell suspension was seeded onto the papillary surface of the acellular porcine dermal matrix, which was made from porcine skin after decellularization with 0.25% trypsin solution and 0.5% Triton X‐100 solution, and cross‐linking with 0.2% glutaraldehyde solution, as previously described 16. Subsequently, these composites were submerged in keratinocyte serum‐free medium for four days cultivation and then, they were lifted to the air‐liquid interface for seven days cultivation.…”
Section: Methodsmentioning
confidence: 99%
“…An RR-like structure has been found in microtextured basal lamina analogues [Downing et al, 2005] and in our previous study on the empty hair follicles of an acellular porcine dermal matrix [Xiong et al, 2008]. However, the native morphology, characteristics, and morphogenesis-related factors of RRs at the dermal-epidermal interface are still unclear and warrant further investigation.…”
Section: Introductionmentioning
confidence: 84%
“…There are several approaches for constructing the microtexture at the epidermal-dermal interface [Pins et al, 2000;Downing et al, 2005;Xiong et al, 2008]. However, the morphological characteristics of native RRs and the expression of ERK1/2, Ki67, and keratin-19 therein are not clear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation